1989
DOI: 10.1111/j.1745-4557.1989.tb00328.x
|View full text |Cite
|
Sign up to set email alerts
|

National Consumer Retail Beef Study: Interaction of Trim Level, Price and Grade on Consumer Acceptance of Beef Steaks and Roasts

Abstract: Consumers in SanFrancisco, California and Philadelphia, Pennsylvania, USA were asked to purchase, in simulated retail markets, beef retail cuts of different grades, Choice versus Select (equivalent to Good), or of different trim levels, Regular Trim (no more than 13 mm of external fat; Philadelphia only), Extra Trim (no more than 8 rnm of external fat) or Super Trim (no external fat), all priced at Parity or Premium (Parity plus 10%) prices. Consumers in Philadelphia purchased signijicantly more Extra Trim and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(86 citation statements)
references
References 1 publication
5
77
1
3
Order By: Relevance
“…At the time of purchase, consumers in both cities could not detect the visual differences in choice v. select, but upon eating them found that choice cuts were better tasting -but also fatter -and that select cuts were leaner -but had problems with taste and texture. Savell et al (1989) concluded from this study that both choice and select were rated high for consumer acceptance but for different reasons -taste for choice, leanness for select. Branson et al (1986) reported results of a retail store pilot test (four supermarkets; 12 weeks/store) that supported the concept that a segmented market existed for beef, and that namebrand lean beef (i.e.…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of purchase, consumers in both cities could not detect the visual differences in choice v. select, but upon eating them found that choice cuts were better tasting -but also fatter -and that select cuts were leaner -but had problems with taste and texture. Savell et al (1989) concluded from this study that both choice and select were rated high for consumer acceptance but for different reasons -taste for choice, leanness for select. Branson et al (1986) reported results of a retail store pilot test (four supermarkets; 12 weeks/store) that supported the concept that a segmented market existed for beef, and that namebrand lean beef (i.e.…”
Section: Palatability Prediction Using Usda Quality Gradesmentioning
confidence: 99%
“…Of factors considered of primary importance in determining tenderness and overall palatability of cooked beef in the MSA grading system, there is ample US research-study support for use of marbling (Smith et al 1969(Smith et al , 2007Savell et al 1987Savell et al , 1989George et al 1999;Wyle 2000;Platter et al 2003bPlatter et al , 2005Gruber et al 2006), maturity (Berry et al 1974a(Berry et al , 1974bSmith et al 1982Smith et al , 1988Smith et al , 2008Hilton et al 1998), amount of B. indicus genetics (McKeith et al 1985a(McKeith et al , 1985bSherbeck et al 1995Sherbeck et al , 1996O'Connor et al 1997), sex (Choat et al 2006;Tatum et al 2007), tenderstretch carcass suspension (Smith et al , 1979(Smith et al , 2007Orts et al 1971;Hostetler et al 1975), ultimate pH (Smulders et al 1990;Tatum 1991a, 1994;Eilers et al 1996;Wulf et al 1997), meat colour (Jeremiah et al 1972;Wulf et al 1997;Cannell et al 2000;Wyle et al 2003;Vote et al 2003), fat colour (Hilton et al 1998;Wyle et al 1998Wyle et al , 2003Wyle 2000;Vote et al 2003) and subcu...…”
Section: Advantages Of the Tqm Approach To Assessing Beef Qualitymentioning
confidence: 99%
“…Meat 267 juiciness plays a key role in meat texture and refers to the mouthfeel of the moisture released 268 during mastication. Thus, juiciness is indicative of the moisture released from meat during 269 chewing and from saliva in response to lipid stimulation (Savell et al, 1989). It was recently 270 suggested that water acts as a plasticizer of muscle proteins and its loss influences structural …”
mentioning
confidence: 99%
“…Results from this study support Savell et al (1991) finding the rib and chuck cuts to have the highest percentages of seam fat. Unlike seam fat, external fat can be removed relatively easily from retail cuts, and after the release of the National Consumer Retail Beef Study (Cross et al, 1986;Savell et al, 1989), retailers made tremendous efforts to decrease the amount of external fat on cuts in the retail case. Innovative fabrication styles are being used more in industry today, and these account for some of the decrease in fat trim levels at retail; however, retailer product specifications have specific external fat thickness requirements for incoming product and may also have contributed to this decrease.…”
Section: Separable Tissue Componentsmentioning
confidence: 99%
“…Several key findings in the beef industry during the late 1980s instigated major changes in the way beef retail cuts have been merchandized and as a consequence made data presented in Agricultural Handbook 8-13 (USDA, 1986) obsolete. The National Consumer Retail Beef Study (Cross, Savell, & Francis, 1986;Savell et al, 1989) showed that consumers preferred beef retail cuts that were trimmed to have little or no subcutaneous fat. These findings led retailers to reduce fat trim specifications to no more than 0.64 cm to meet consumer demands (Cross et al, 1986).…”
Section: Introductionmentioning
confidence: 99%